2022
DOI: 10.3389/fnut.2022.907789
|View full text |Cite
|
Sign up to set email alerts
|

Higher Circulating Vitamin D Levels Are Associated With Decreased Migraine Risk: A Mendelian Randomization Study

Abstract: BackgroundEvidence showed the supplementation of vitamin D might have beneficial effects for migraine patients. We aimed to investigate the causal effects of serum vitamin D levels on migraine risk using two-sample Mendelian randomization (MR) method.MethodsA total of 184 independent genetic instruments for serum vitamin D levels were selected from a study in 417,580 Europeans from UK biobank. Six variants from an independent study were obtained to perform replication analysis. Summary-level data for migraine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…A recent meta‐analysis of previous publications confirmed decreased serum 25‐hydroxyvitamin D levels in patients with migraine compared with controls 11 . Finally, a Mendelian randomization study involving three migraine datasets (48,975, 28,852, and 10,536 cases each) described an association between increased serum vitamin D levels and decreased risk for migraine 12 …”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…A recent meta‐analysis of previous publications confirmed decreased serum 25‐hydroxyvitamin D levels in patients with migraine compared with controls 11 . Finally, a Mendelian randomization study involving three migraine datasets (48,975, 28,852, and 10,536 cases each) described an association between increased serum vitamin D levels and decreased risk for migraine 12 …”
Section: Introductionmentioning
confidence: 86%
“…11 Finally, a Mendelian randomization study involving three migraine datasets (48,975,28,852, and 10,536 cases each) described an association between increased serum vitamin D levels and decreased risk for migraine. 12 Buettner et al 13 described decreased risk for a headache of migraine type (although not with the severity of headache) in subjects with higher serum levels of vitamin D and statin use, in a series of 5938 participants. Serum vitamin D receptor levels have been found to be decreased, and serum vitamin D-binding protein levels are similar in migraine patients compared with controls in a single study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose the 123 SNPs as candidate genetic instruments. We further performed a linkage disequilibrium clumping procedure using a wide, 10-Mb window and a stringent linkage disequilibrium threshold ( r 2 = 0.01) to identify independently significant SNPs ( Niu et al, 2022 ). The reference panel used was the European 1,000 Genome Project v3.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported that vitamin D low-serum levels may be associated with an increased risk of migraines/headaches [189]. In addition, it has been suggested that the prevalence of a deficiency/insufficiency of vitamin D may be greater in patients suffering from migraines/headaches when compared with subjects without headaches [190].…”
Section: Vitamin D Supplementationmentioning
confidence: 99%